Studi Fenomenologi: Kehamilan Tidak Diinginkan dan Penggunaan IUD pada Ibu Nifas Remaja - Ade Tasya Rosalina; Anjali Fisalafi Shomad; Rinda Sari; Anis Ardiyanti; Wahyu Cholid Nugroho Sakti (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Unintended pregnancy among adolescents remains a significant reproductive health concern, affecting physical, psychological, and social well-being and often influenced by sociocultural factors. Postpartum intrauterine device (IUD) insertion is a long-acting reversible contraceptive method intended to prevent rapid repeat pregnancies; however, the lived experiences of adolescent postpartum IUD users remain underexplored. This case study aimed to gain an in-depth understanding of the psychological impact and reproductive well-being of a adolescent postpartum IUD user with a history of unintended pregnancy at one of the community health centers in Semarang city, Indonesia. This study employed a qualitative approach using Interpretative Phenomenological Analysis (IPA). Data were collected through semi-structured in-depth interviews, complemented by a review of medical records and family planning counseling documents. Data analysis involved repeated reading of transcripts, identification of emergent themes, and interpretative exploration of the participant’s lived experiences. Five major themes emerged from the analysis: (1) inadequate reproductive health knowledge as a primary contributor to unintended pregnancy; (2) the influence of parental and environmental factors on adolescent unintended pregnancy; (3) loss of access to administrative and social protection due to the prevailing culture of shame surrounding adolescent pregnancy; (4) increased vulnerability to postpartum blues among adolescents experiencing unintended pregnancy; and (5) insufficient understanding of IUD contraception leading to discomfort and challenges in its use. The findings highlight the importance of comprehensive reproductive health education, family involvement, psychosocial support, and effective contraceptive counseling to improve reproductive well-being and contraceptive experiences among adolescents with unintended pregnancies.